Development of educational multimedia to improve the understanding of nature conservation: A study of Gunung Gede Pangrango National Parks conservation volunteers - Ika Rosmalasari; Rita Retnowati; Herfina Herfina (Indonesian Journal of Applied Environmental Studies, 2020)
The purpose of this research is to develop a multimedia conservation of education application, and to determine its effectiveness in understanding the nature conservation of conservation cadres or volunteers in the national park area. This research used the Research and Development method of the model Borg Gall which was modified into five stages, were Research and Information Collecting, Planning, Developing Preliminary of Product, Preliminary Field Testing and Main Product Revision.  While the application development stage used the SDLC (System Development Life Cycle) method which consisted of planning, analysis, design, implementation and testing stages. Data obtained from the validation of material experts and multimedia experts. The effectiveness test used the analysis of the N-Gain value of each indicator of the pretest and posttest questions. To develop educational multimedia applications need to analysis, preparing the designs and materials, developing the application, validating applications by experts, assessing the quality of application systems, small and large scaling field trials and evaluation. The purpose research product is the digital information entitled E-Info of Nature Conservation Media which can be accessed free of charge via the link (ika.gedepangrango.org).  According to data analysis we concluded that the development of educational multimedia applications can increase understanding of nature conservation for conservation volunteers in the national park area. The Scores pretest and posttest obtained an average N-Gain score of 0.73 and a percentage score of 73.33% with the criteria ``High" and the criteria "Quite Effective", which means E-Info Application The media developed is suitable to be applied and quite effective in increasing respondents' understanding of conservation.Tujuan dari penelitian ini adalah untuk mengembangkan aplikasi multimedia edukasi konservasi dan untuk mengetahui tingkat efektivitasnya terhadap pemahaman konservasi alam para kader konservasi di wilayah taman nasional. Penelitian ini menggunakan metode Research and Development model Borg Gall yang dimodifikasi menjadi lima tahapan yaitu Research and Information Collecting, Planning, Develop Preliminary of Product, Preliminary Field Testing dan Main Product Revision. Sedangkan tahapan pengembangan aplikasinya menggunakan metode SDLC (System Development Life Cycle) yang terdiri dari tahapan perencanaan, analisis, desain, implementasi dan tesing. Data diperoleh dari hasil validasi dua ahli yaitu ahli materi dan ahli multimedia. Uji keefektifan menggunakan analisis nilai N-Gain dari setiap indikator soal pretest dan posttest. Langkah-langkah untuk mengembangkan aplikasi multimedia edukasi yaitu analisis kebutuhan, penyusunan desain dan materi, pengembangan aplikasi, memvalidasi aplikasi oleh para ahli, penilaian kualitas sistem aplikasi, uji coba lapangan skala kecil dan skala luas serta evaluasi. Produk yang dihasilkan adalah informasi digital berjudul E-Info Media Konservasi Alam yang dapat diakses secara gratis melalui link (ika.gedepangrango.org). Berdasarkan analisis data  disimpulkan bahwa pengembangan aplikasi multimedia edukasi dapat meningkatkan pemahaman konservasi alam bagi para kader konservasi di wilayah taman nasional. Skor pretest dan posttest diperoleh rata-rata skor N-Gain yaitu 0,73 dan skor prosentase 73,33% dengan kriteria Tinggiâ€ dan kriteria Cukup Efektifâ€ yang artinya Aplikasi E-Info Media yang dikembangkan layak untuk digunakan dan cukup efektif dalam meningkatkan pemahaman konservasi responden.